2017
DOI: 10.1158/0008-5472.can-17-0286
|View full text |Cite
|
Sign up to set email alerts
|

STRAP Promotes Stemness of Human Colorectal Cancer via Epigenetic Regulation of the NOTCH Pathway

Abstract: NOTCH signaling exerts essential roles in normal and malignant intestinal physiology and the homeostasis of cancer stem-like cells (CSC), but the basis for this latter role remains obscure. The signaling scaffold protein STRAP is upregulated in several cancers where it promotes tumorigenicity and metastasis. Here we report a novel oncogenic function for STRAP in maintaining CSC subpopulations in a heterogeneous mixture by antagonizing formation of the chromatin modifier PRC2 and by epigenetically activating NO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 44 publications
1
59
0
Order By: Relevance
“…These results suggest that one mechanism by which elevated STRAP expression supports HCC growth is to shift the balance toward the induction of stem cell features. This observation is in line with the work of Jin and colleagues who showed that STRAP promotes stem cell features in several colorectal cancer cell lines (33). Besides its role in fine-tuning b-catenin signaling, STRAP has also been linked to various other cellular processes likely con-tributing to HCC cell viability (9,14).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results suggest that one mechanism by which elevated STRAP expression supports HCC growth is to shift the balance toward the induction of stem cell features. This observation is in line with the work of Jin and colleagues who showed that STRAP promotes stem cell features in several colorectal cancer cell lines (33). Besides its role in fine-tuning b-catenin signaling, STRAP has also been linked to various other cellular processes likely con-tributing to HCC cell viability (9,14).…”
Section: Discussionsupporting
confidence: 87%
“…In particular, Wnt/b-catenin-driven AXIN2 þ (31) and LGR5 þ (32) cells have been identified as stem cells that self-renew and give rise to mature hepatocytes. STRAP itself has also been linked to stemness in colorectal cancer (33). Therefore, loss of STRAP and the resulting reduction in b-catenin signaling may lead to reduced expression of stem/ progenitor cell markers.…”
Section: Loss Of Strap Associates With Reduced Stemness and Increasedmentioning
confidence: 99%
“…The NOTCH pathway has been reported to modulate the homeostasis of cancer stem cell-like cells (CSCs) in colorectal cancer [43]. Miranda Brun et al found that HEY1 was associated with increased proliferation and stem cell characteristics in GBM cells [44].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, alterations in FBXW7 have been related to liver metastasis and prognosis of CRC . The expression of another WDR domain protein, STRAP, was increased in CRC and promoted stemness of CRC via regulation of NOTCH signaling . Other WDR domain proteins, such as WDR13, DCAF4L2, WDR48, Bop1, CIRH1A, DTL, and EIF3B, have also been shown to be involved in the development and progression of CRC .…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] The expression of another WDR domain protein, STRAP, was increased in CRC and promoted stemness of CRC via regulation of NOTCH signaling. [19][20][21] Other WDR domain proteins, such as WDR13, DCAF4L2, WDR48, Bop1, CIRH1A, DTL, and EIF3B, have also been shown to be involved in the development and progression of CRC. [22][23][24][25][26][27][28] Recently, two WDR domain proteins, WDR5 and EDD, were successfully targeted by drug-like chemical probes.…”
Section: Introductionmentioning
confidence: 99%